Bosentan For Digital Ulcers in Patients With Systemic Sclerosis: Single Center Experience - Orhan KÜÇÜKŞAHİN and Mustafa Turgut YILDIZGÖREN and Demet Menekşe GEREDE and Yüksel MARAŞ and Şükran ERTEN (Archives of Rheumatology, 2016)
Objectives: This study aims to investigate the effects of bosentan on the prevention and treatment of digital ulcers in systemic sclerosis (SSc) patients. Patients and methods: The study included 30 patients (4 males, 26 females; mean age 49.6±15.4 years; range 23 to 71 years) diagnosed with SSc and treated with bosentan for digital ulcers. Bosentan was administered to all patients for a mean of 14±10.3 months. All SSc cases were refractory to calcium channel antagonists or angiotensin II inhibitors. The diagnosis of SSc was based on the American College of Rheumatology criteria and patients were classified as limited or diffuse cutaneous SSc according to the LeRoy classification. Results: Mean disease duration was 8.8±8.0 years and mean duration of digital ulcers was 29.4±6.6 months. Under the bosentan treatment, eight patients (26.7%) developed new digital ulcers; all of these patients had diffuse cutaneous SSc. Health Assessment Questionnaire scores improved after 12 months and 24 months of treatment (p<0.001). Three patients (10%) developed pulmonary arterial hypertension under bosentan treatment [two patients (6.6%) had SSc-associated pulmonary arterial hypertension and one patient (3.3%) had interstitial fibrosis-associated pulmonary arterial hypertension]. The anti-centromere antibody positive patients were predominantly classified as limited cutaneous SSc. Of the patients positive for anti-topoisomerase-1 antibodies, a high proportion was classified as diffuse cutaneous SSc. Pulmonary fibrosis was most frequent in the anti-topoisomerase-1 antibody subset. New digital ulcers developed mainly in the anti-topoisomerase-1 antibody positive patients. Conclusion: Bosentan may be used either alone or in combination with other treatments when digital ulcers worsen and may be expected to suppress the development of new ulcers and severe pain. Further preclinical studies are required shedding light on the etiopathogenesis of SSc and larger clinical trials are needed for more definitive treatment strategies.